Voting But for the Law: Evidence from Virginia on Photo Identification Requirements. Issue 1 (March 2017) - Hopkins, Daniel J.; Meredith, Marc; Morse, Michael; Smith, Sarah; Yoder, Jesse
Abstract : One contentious question in contemporary election administration is the impact of voter identification requirements. We study a Virginia law that allows us to isolate the impact of requiring voters to show photo identification. Using novel, precinct‐level data, we find that the percentage of registered voters without a driver's license and over age 85 are both positively associated with the number of provisional ballots cast due to a lack of a photo ID. To examine the law's impact on turnout, we associate precinct‐level demographics with the change in turnout between the 2013 gubernatorial and 2014 midterm elections. All else equal, turnout was higher in places where more active registered voters lacked a driver's license. This unexpected relationship might be explained by a targeted Department of Elections mailing, suggesting that the initial impact of voter ID laws may hinge on efforts to notify voters likely to be affected.